2018
DOI: 10.1016/j.bbi.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Inflammatory Index is associated with elevated white blood cell counts in the National Health and Nutrition Examination Survey

Abstract: White blood cells (WBCs) are considered a reliable biomarker of inflammation. Elevations in both WBCs and pro-inflammatory cytokines are associated with several chronic conditions. Diet is a strong moderator of inflammation and WBCs. The purpose of this study was to examine the association between the Dietary Inflammatory Index (DII®) and WBCs using data from the United States National Health and Nutrition Examination Survey (NHANES). NHANES is a cross-sectional study that occurs in two-year cycles. Respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 61 publications
0
44
0
Order By: Relevance
“…Increasing evidence suggests that some foods, food components and nutrients may modulate inflammatory status [ 13 , 14 ]. Supporting that concept are the findings that the DII has been associated with circulating concentrations of CRP [ 16 , 17 , 18 ], IL-6 [ 19 , 20 ], TNF-α [ 19 ] and WBC counts [ 22 ]. Examination of pro-inflammatory cytokines, acute-phase response proteins, adipocytokines and WBC profiles of the study population stratified by E-DII median in the present work revealed higher C3, CRP, IL-6 and TNF-α concentrations and WBC counts (due to elevated neutrophils, monocytes and basophils), higher NLR and lower adiponectin levels among those with higher E-DII scores (top 50th percentile) relative to their counterparts with lower E-DII scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that some foods, food components and nutrients may modulate inflammatory status [ 13 , 14 ]. Supporting that concept are the findings that the DII has been associated with circulating concentrations of CRP [ 16 , 17 , 18 ], IL-6 [ 19 , 20 ], TNF-α [ 19 ] and WBC counts [ 22 ]. Examination of pro-inflammatory cytokines, acute-phase response proteins, adipocytokines and WBC profiles of the study population stratified by E-DII median in the present work revealed higher C3, CRP, IL-6 and TNF-α concentrations and WBC counts (due to elevated neutrophils, monocytes and basophils), higher NLR and lower adiponectin levels among those with higher E-DII scores (top 50th percentile) relative to their counterparts with lower E-DII scores.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data exist regarding the associations between dietary inflammatory potential, circulating biomarkers of cardiometabolic health and MetS risk. Thus far, the DII has been associated with C-reactive protein (CRP) [ 16 , 17 , 18 ], interleukin (IL)-6 [ 19 , 20 ], tumour necrosis factor (TNF)-α [ 19 ], fibrinogen [ 21 ] and more recently with white blood cell (WBC) counts [ 22 ]. To date, six studies have examined the association between the DII and MetS risk, with inconsistent relationships identified [ 16 , 18 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This index is a useful tool to predict the level of inflammatory cytokines such as IL6, CRP, and health indices based on the score of dietary inflammation 29 . Studies have shown that higher levels of DII maybe correlate with elevated levels of serum inflammatory factors such as IL-6, CRP, fibrinogen, homocysteine, TNF-α 13,19,23,30 , and white blood cell count (WBC) 31 . In this regard, several studies have reported a significant relationship between diet and inflammatory factor 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We also have tested effects on other markers of disease risk such as homocysteine, chemerin, fibrinogen, complement component C3, leukocytes/white blood cells, interferons, intercellular adhesion molecule, and vascular cell adhesion molecule 1 [31,33,41]. The DII or energy-adjusted DII (E-DII) have been construct validated against inflammatory biomarkers in different populations and under varying conditions [12,29,31,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. More recently the children’s DII (C-DII) has been developed and construct validated with hs-CRP in an American study [49].…”
Section: DII Developmentmentioning
confidence: 99%